Variation in Some Structural, Biochemical and Gas Exchange Characteristics of Sun and Shade Leaves of Vernonia amygdalina - Idris, Aisha; Cuevas Linatoc, Alona; Muhammad Aliyu, Aisha; Mustapha Muhammad, Surayya (International Journal of Psychosocial Rehabilitation, 2020)
Light intensity has an influence on the photosynthetic capacity of a plant. The objective of this research was to investigate the variation in some structural, biochemical, and gas exchange characteristics of sun and shade leaves of Vernonia amygdalina. Sun and shade leaves were studied, and their light response parameters, including light saturation point (LSP), light compensation point (LCP), and apparent quantum yield, were estimated. Photosynthetic pigments were quantified spectrophotometrically. The stomatal density was determined using the nail polish method and examined using a light microscope. The result of this study proves that high light intensity influences gas exchange, stomatal density, leaf thickness, and photosynthetic pigment of the studied plant. As the light intensity increases, Amax, LSP, and LCP increase. There are significant differences between the light response characteristics, photosynthetic pigment, and stomatal density of sun and shade leaves (P